1999
DOI: 10.1073/pnas.96.4.1439
|View full text |Cite
|
Sign up to set email alerts
|

The molecular chaperone Hsp90 can negatively regulate the activity of a glucocorticosteroid-dependent promoter

Abstract: Hsp90, a molecular chaperone required for the functioning of glucocorticosteroid receptor (GR), ensures, by direct interaction, the conformational competence of the steroid-binding pocket. In addition to having this positive function, Hsp90 maintains steroid receptors in an inactive form in the absence of hormone. However, neither the participation of Hsp90 once the pathway has been activated by the ligand nor the importance of increased Hsp90 levels in determining the amplitude of the response has ever been a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 39 publications
3
52
0
Order By: Relevance
“…There is recent evidence that the latter inhibitory function of Hsp 90 prevails when Hsp 90/GR ratio is highly increased, especially in the nucleus (47). Thus, whether Hsp 90 accumulation following calpain inhibition increases glucocorticoid responsiveness in addition to glucocorticoid binding was questionable.…”
Section: Discussionmentioning
confidence: 99%
“…There is recent evidence that the latter inhibitory function of Hsp 90 prevails when Hsp 90/GR ratio is highly increased, especially in the nucleus (47). Thus, whether Hsp 90 accumulation following calpain inhibition increases glucocorticoid responsiveness in addition to glucocorticoid binding was questionable.…”
Section: Discussionmentioning
confidence: 99%
“…HM9-binding site to compete with the coactivator LxxLL motifs for binding to the hydrophobic groove provides a potential explanation for the observed ability of Hsp90 to inhibit the transcriptional activity of GR (11,13). These interactions of Hsp90 with apo-and holo-GR appear to optimize the transition between inactive and active states of GR, resulting in a sharpening of the cellular response to hormone.…”
Section: Discussionmentioning
confidence: 99%
“…Hormone binding by GR induces the replacement of the GR-Hsp90 heterocomplex component FKBP51 by FKBP52, whose interaction with the motor protein dynein has been implicated in the nuclear import of holo-GR (9-10). Hsp90 and p23 are present at glucocorticoid response elements (GREs) and regulate the interaction of GR with GREs and transcriptional coregulators (11)(12)(13).…”
mentioning
confidence: 99%
“…There is increasing evidence that (co)chaperones are not only important for GR activity in the cytosol, but also in the nucleus. For example, hsp90 may participate in the nuclear-cytoplasmic shuttling of GR (Kang et al 1999) and it may also facilitate chromatin recycling of GR (Liu and DeFranco 1999). More recently, the cochaperone RAP 46 (also known as HAP 46 or BAG-IL) which can associate with hsp90 and GR has been identified as a non-specific DNA-binding protein which may act as a general transcriptional activator (Zeiner et al 1999), on the other hand, Schneikert and coworkers (1999) reported that RAP 46 downregulates GR-mediated transactivation, but not transrepression.…”
Section: Cytosolic Activitiesmentioning
confidence: 99%